Recycled aggregate in concrete : use of industrial, construction and demolition waste - Brito, Jorge de.; Saikia, Nabajyoti (London : Springer, 2013)
This book focuses on the recent developments in the use of various types of recycled waste materials as aggregate in the production of various types of concrete--
Includes bibliographical references and index.
Keywords: Aggregates (Building materials) -- Recycling; Concrete -- Recycling